A process of demographic and economic polarization in the Republic of Macedonia - Madzevic, Mirjanka; Apostolovska Toshevska , Biljana; Iliev, Dejan (UNIVERSITY OF NOVI SAD, FACULTY OF SCIENCE, DEPARTMENT OF GEOGRAPHY, TOURISM & HOTEL MANAGEMENT, 2013)
Demographic and economic development in the Republic of Macedonia is characterized by high dynamics, and imbalance in development. The unequal social and economic development is one of the main negative features of development, especially during the transition period in which the regional development has been marginalized on the expense of market development and stabilization and restructuring of the economy. Equally important component of the development is the problem of concentration and dispersion of population and economic activities in the area causing the appearance of demographic and economic polarization in the country. Today, the degree of the population and economic development in the Republic of Macedonia shows certain differences on a regional level, according to distribution of the population, investments, GDP and etc. From the available social and economic indicators can be concluded that the Republic of Macedonia has the characteristics of a country with a mono-centric model of development where the Skopje region stands out as the core of development, while other regions stagnate or grow with less intensity compared to the previous one. Therefore, this current problem requires finding solutions for reducing the disparities in the regional development and harmonization of the same.
Keywords: Macedonia, population, economic, polarization